PES-Ag3PO4/g-C3N4 mixed matrix film photocatalyst for degradation of methyl orange dye - Mohamad Mukhair, Hayati; Abdullah, Abdul Halim; Zainal, Zulkarnain; Lim, Hong Ngee (MDPI AG, 2021)
In the present study, we explored the effectiveness of PES-Ag3PO4/g-C3N4 film photocatalyst in degrading methyl orange dye under visible light irradiation. The PES-Ag3PO4/g-C3N4 film photocatalyst was prepared via a non-solvent-induced phase inversion process and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), laser scanning microscopy (LSM), X-ray photoelectron spectra (XPS), UV-diffuse reflectance (DRS), and water contact angle. The incorporation of the Ag3PO4/g-C3N4 composite into the PES matrix improved the pristine PES film’s hydrophilicity, as evidenced by the reduction of water contact angle from 79.03° to 54.33° for a film containing 15 wt % of Ag3PO4/g-C3N4 composite. The film’s photoactivity showed that 13 wt % was the best loading of Ag3PO4/g-C3N4 composite, and the degradation performance was maintained up to three cycles. The •O2− and h+ were the predominant species responsible for the methyl orange degradation.